THE ROLE OF FORENSIC PSYCHOLOGY IN CRIMINAL JUSTICE: ANALYZING EXPERT TESTIMONIES AND THEIR IMPACT ON VERDICTS - Juminarseh; Faisal Razak; Adam Idris (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Forensic psychology has become an integral component of modern criminal justice systems, particularly through the use of expert testimony to address complex issues related to mental state, criminal responsibility, competency, and risk assessment. Courts increasingly rely on forensic psychological expertise to inform judicial reasoning, yet the extent and nature of its influence on verdict outcomes remain insufficiently examined. This study aims to analyze the role of forensic psychology in criminal justice by examining how expert psychological testimonies are presented, interpreted, and utilized in judicial verdicts. A qualitative-dominant mixed-method research design was employed, drawing on secondary data from criminal court cases that involved forensic psychological expert testimony. Data were collected through systematic document analysis of court transcripts, expert reports, and written verdicts, supported by descriptive and inferential statistical analysis of verdict patterns. The results indicate that forensic psychological expert testimony significantly influences verdict outcomes, particularly in cases involving criminal responsibility and competency to stand trial. Judicial reliance on expert testimony was strongest when assessments were methodologically rigorous and explicitly referenced in verdict reasoning. The study concludes that forensic psychology functions as a decisive interpretive framework in complex criminal cases rather than as merely supplementary evidence. These findings underscore the importance of methodological rigor, transparency, and ethical accountability in forensic psychological practice to support fair and evidence-based judicial decision-making.